Interleukin 1 (IL-1) and tumour necrosis factor synergise in the induction of IL-1 synthesis by human vascular endothelial cells. - Howells, G; Chantry, D; Feldmann, M (1988)
We have demonstrated that recombinant interleukin 1 (IL-1) induces IL-1 alpha and IL-1 beta production by human vascular endothelial cells (EC) in vitro. The effect of IL-1 on EC was dose-dependent and not due to contamination by endotoxin or secondary to the production of tumour necrosis factor (TNF). Thymocyte co-mitogenesis was shown to be due to IL-1 by treating EC supernatants with neutralising antibodies specific for IL-1 alpha and IL-1 beta. Recombinant TNF alpha synergised with IL-1 in the induction of IL-1 secretion by EC. Synergy was particularly striking at concentrations of IL-1 and TNF which, when used alone, had no effect - 2 U/ml IL-1 with 10 U/ml TNF. Thus we provide more evidence that EC play an important role in the perpetuation or possibly even initiation of chronic inflammation by amplifying cytokine production initiated by small numbers of infiltrating leucocytes.